Eksistensi Putusan Mahkamah Konstitusi Pasca Disahkannya Undang-Undang Penetapan Perpu Cipta Kerja - Suhardin, Yohanes; Flora, Henny Saida (Universitas Semarang, 2023)
This study aims at analyzing the existence of Constitutional Court Ruling No. 91/PUU-XVIII/2020 (Job Creation MK Decision) after Law No. 6 of 2023 concerning Job Creation. This research is a normative legal research by prioritizing case approaches, concepts, and legislation. The results of the study confirmed that the existence of the Job Creation MK Decision after the passage of the Job Creation Law was as if the Job Creation MK Decision was between